PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ANGKASA PURA II BANDAR UDARA SULTAN SYARIF KASIM II PEKANBARU - Sari, Siti Dwi Intan; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at PT. Angkasa Pura II Airport Sultan Syarif Kasim II Pekanbaru as the purpose of this study was to determine the effect of compensation and work motivation on the performance of employees of PT.Angkasa Pura II. Compensation and Work Motivation as independent variables (X1X2) while Employee Performance is the dependent variable (Y). The problem in this study is the performance of employees of PT. Angkasa Pura II. Not as expected by the company. The sample of this study was taken as many as 79 respondents from the population calculated using the Slovin formula. The data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS program. From the results of the tests performed showed that Work Compensation and Motivation had a positive and significant effect on Employee Performance of PT. Angkasa Pura II Pekanbaru.Keywords: Compensation, Work Motivation and Employee Performance